2020
DOI: 10.1007/s00403-020-02121-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tacrolimus plus phototherapy in the treatment of vitiligo: a meta-analysis

Abstract: The objective of this meta-analysis was performed to compare the effects of tacrolimus plus phototherapy in the treatment of patients with vitiligo. Relevant studies were identified by searching PubMed, Embase, and Web of Science databases. The main outcomes of interest included excellent response (≥ 75% repigmentation), good response (50-75% repigmentation), moderate response (25%-50% repigmentation), and poor response (< 25% repigmentation). Risk ratio (RR) with 95% confidence intervals (95% CIs) was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
1
13
1
Order By: Relevance
“…29,30 In addition, TCI protects the skin against UV damage, helps prevent UV-associated erythema by inhibiting the early inflammatory process, increases the skin's tolerance, and reduces the damage caused by photoaging. 22 In our study, the cumulative dose in the experimental group was also higher than that in the control group, and there was no severe photodamage in both groups, but mild erythema and desquamation. Moreover, Tran et al found that the pretreatment of TCI inhibited the formation of UV-mediated thymine dimer in the epidermis of hairless mice in comparison to the untreated control group, indicating that TCI has a protective biological effect on UV-mediated DNA damage, decreasing the risk of malignancies, 31 offering a better guarantee of safety for 308-nm EL in treating periocular vitiligo.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…29,30 In addition, TCI protects the skin against UV damage, helps prevent UV-associated erythema by inhibiting the early inflammatory process, increases the skin's tolerance, and reduces the damage caused by photoaging. 22 In our study, the cumulative dose in the experimental group was also higher than that in the control group, and there was no severe photodamage in both groups, but mild erythema and desquamation. Moreover, Tran et al found that the pretreatment of TCI inhibited the formation of UV-mediated thymine dimer in the epidermis of hairless mice in comparison to the untreated control group, indicating that TCI has a protective biological effect on UV-mediated DNA damage, decreasing the risk of malignancies, 31 offering a better guarantee of safety for 308-nm EL in treating periocular vitiligo.…”
Section: Discussionsupporting
confidence: 46%
“…Although various methods have been proposed to treat vitiligo, such as topical medications, phototherapy and surgery transplant, there is no single treatment that can achieve repigmentation and prevent recurrence in all patients 21 . Dong et al 22 proposed that the treatment of vitiligo needs to meet the two following conditions: inhibit the excessive immune response in the affected region to prevent the progression of the vitiligo; stimulate the proliferation, differentiation and migration of melanocytes and melanin stem cells for repigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical calcineurin inhibitors have the potential to stimulate melanocyte growth and migration 8 . Furthermore, calcineurin inhibitors do not cause skin atrophy, and even may reduce NB‐UVB‐induced erythema, 12 which is one of the few potential adverse effects of NB‐UVB therapy. There is a theoretical risk of skin cancer with use of topical calcineurin inhibitors, however, studies have demonstrated tacrolimus may actually be protective against skin carcinomas due to its inhibition of thymine dimer formation after ultraviolet light exposure 8,13 …”
Section: Combination Therapymentioning
confidence: 99%
“…Dong et al 12 conducted a meta‐analysis of 11 studies and found a statistically significant increase in the “excellent response” rate (at least 75% repigmentation) when NB‐UVB and tacrolimus were combined. Subgroup analysis showed that a significant increase in repigmentation rates was observed for combination therapy only when it was applied to the face (relative risk (RR) = 1.60) and proximal limbs (RR = 2.76), but not for the trunk, hands and feet.…”
Section: Combination Therapymentioning
confidence: 99%